To be or not to be on: aspirin and coronary artery bypass graft surgery - Gupta, Aashray K.; Kovoor, Joshua G.; Leslie, Alasdair; Litwin, Peter; Stretton, Brandon; Zaka, Ammar; Kovoor, Pramesh; Bacchi, Stephen; Bennetts, Jayme S.; Maddern, Guy J. (Frontiers in Cardiovascular Medicine, 2024)
Aspirin's role in secondary prevention for patients with known coronary artery disease (CAD) is well established, validated by numerous landmark trials over the past several decades. However, its perioperative use in coronary artery bypass graft (CABG) surgery remains contentious due to the delicate balance between the risks of thrombosis and bleeding. While continuation of aspirin in patients undergoing CABG following acute coronary syndrome is widely supported due to the high risk of reinfarction, the evidence is less definitive for elective CABG procedures. The literature indicates a significant benefit of aspirin in reducing cardiovascular events in CAD patients, yet its impact on perioperative outcomes in CABG surgery is less clear. Some studies suggest increased bleeding risks without substantial improvement in cardiac outcomes. Specific to elective CABG, evidence is mixed, with some data indicating no significant difference in thrombotic or bleeding complications whether aspirin is continued or withheld preoperatively. Advancements in pharmacological therapies and perioperative care have evolved significantly since the initial aspirin trials, raising questions about the contemporary relevance of earlier findings. Individualized patient assessments and the development of risk stratification tools are needed to optimize perioperative aspirin use in CABG surgery. Further research is essential to establish clearer guidelines and improve patient outcomes. The objective of this review is to critically evaluate the existing evidence into the optimal management of perioperative aspirin in elective CABG patients.